An agent that understands job description - Bežek, Andraž (Informatica (Ljubljana), 2001)
An important property of intelligent agents is semi-understanding of desired tasks. We have designed an agent module referred to as Professional Description Assistant that is able to identify the corresponding job definition from a job description in textual form. Thus it plays a significant role in the advanced services of our EMA employment agent. By means of some standard and modified learning methods the findings proved to be quite encouraging. The new function aids the user performing some standard tasks, which normally demand human decision and experience to a great extent.
Keywords: umetna inteligenca; inteligentni agenti; razum; reason; inteligentni servisi